2018
DOI: 10.1681/asn.2018050519
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Anti-Peroxidasin Antibodies in Pulmonary-Renal Syndromes

Abstract: Background Goodpasture syndrome (GP) is a pulmonary-renal syndrome characterized by autoantibodies directed against the NC1 domains of collagen IV in the glomerular and alveolar basement membranes. Exposure of the cryptic epitope is thought to occur via disruption of sulfilimine crosslinks in the NC1 domain that are formed by peroxidasin-dependent production of hypobromous acid. Peroxidasin, a heme peroxidase, has significant structural overlap with myeloperoxidase (MPO), and MPO-ANCA is present both before an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 28 publications
0
20
1
Order By: Relevance
“…Some researchers have observed that, in addition to their inflammatory profile, AAV patients have neutrophils with a high apoptosis rate and reduced activation capacity [37], which may contribute to their diminished ability to contain or eliminate bacterial pathogens. Some researchers recently detected inhibitory anti-peroxidasin autoantibodies present in serum from patients before and at the onset of anti-GBM disease [38]. Peroxydasin shares structural homology with MPO, and anti-peroxidasin autoantibodies cross-react in vitro with MPO, which could account for some "false" MPO positive patients [39].…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have observed that, in addition to their inflammatory profile, AAV patients have neutrophils with a high apoptosis rate and reduced activation capacity [37], which may contribute to their diminished ability to contain or eliminate bacterial pathogens. Some researchers recently detected inhibitory anti-peroxidasin autoantibodies present in serum from patients before and at the onset of anti-GBM disease [38]. Peroxydasin shares structural homology with MPO, and anti-peroxidasin autoantibodies cross-react in vitro with MPO, which could account for some "false" MPO positive patients [39].…”
Section: Discussionmentioning
confidence: 99%
“…Although the AAVs are typically considered systemic autoimmune diseases, each with dominant autoreactivity to only a single autoantigen, other autoantigens have been associated with AAV. These autoantigens include lysosome-associated membrane protein 2 (LAMP2) 54 , complementary PR3 (cPR3) peptides 55,56 , moesin 57 , plasminogen 58,59 , peroxidasin 60 and pentraxin 3 (reF. 61 ).…”
Section: Anca Antigensmentioning
confidence: 99%
“…PXDN is expressed in endothelial cells, epithelial cells, and fibroblasts. Relatively high expression of PXDN is observed in several human tissues such as the heart, spleen, kidney, and lung [17,18]. As PXDN stabilizes Col IV, a major component of BM, its deficiency in lower animals leads to lethality because of disorganized tissue structures.…”
Section: External Morphological Defect Was Obvious In Eyes But Not Omentioning
confidence: 99%